Exogenous Silicon Enhanced Salt Resistance by Maintaining K+/Na+ Homeostasis and Antioxidant Performance in Alfalfa Leaves - Meng, Yuanfa; Yin, Qiang; Yan, Zhijian; Wang, Yuqing; Niu, Jianming; Zhang, Jie; Fan, Kai (Frontiers in Plant Science, 2020)
Silicon (Si) has been known to improve salt tolerance in plants. In this study, 4-weeks-old alfalfa seedlings were exposed to various concentrations of external NaCl (0-200mM) with or without 2mM Si in the form of sodium metasilicate Na2SiO3•5H2O for 2 weeks. The results showed that NaCl-stressed plants showed a decrease in growth parameters, stem extension rate, predawn leaf water potential (LWP) and the chlorophyll content, potassium (K+) concentration, as well as potassium/sodium ion (K+/Na+) ratio. By contrast, NaCl-stressed plants increased the Na+ concentration and malondialdehyde (MDA) level, as well as the activities of superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) in alfalfa leaves. On the other hand, exogenously applied Si enhanced photosynthesis parameters of NaCl-stressed plants, which was accompanied by the enhancement in predawn LWP, level of chlorophyll content and WUE, The Si-treated plants displayed enhanced salinity tolerance by limiting Na+ accumulation while maintaining K+ concentration in leaves, the increased K+/Na+ radio established an ion homoeostasis to protect the leaves from toxic Na+ and thereby maintained higher chlorophyll retention. Simultaneously, Si-treated plants showed higher antioxidant activities and decreased MDA level under salt stress. It is concluded that Si enhanced salt tolerance of alfalfa though improving the leaves photosynthesis by enhancing antioxidant performance and maintaining ion homoeostasis in leaves. Take together, our data showed that exogenous silicon application could be effectively manipulated for improving salt tolerance of alfalfa grown in saline soil.